Turkey's economic rapprochement towards Syria and the territorial conflict over Hatay. Issue 1 (1st January 2019) - Magued, Shaimaa
Abstract: This article addresses the Justice and Development Party's economic rapprochement towards Syria since 2002. While, the literature tackling the Turkish economic foreign policy has mainly focused on the reasons behind the rise of Turkey's trade, this study argues that Turkey's economic policy contributed to the alleviation of the Hatay issue, a historical territorial conflict that marked bilateral relations for long decades.